2004
DOI: 10.1002/eji.200324303
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T cells contribute to airway eosinophilic inflammation induced by ragweed through enhanced IL‐4 and eotaxin production

Abstract: Although NKT cells have been found to be capable of modulating immune responses in several model systems, the role of NKT cells in allergy remains unclear. Using CD1 gene knockout (KO) mice, which lack NKT cells, we examined the function of NKT cells in the development of allergic inflammation induced by a common airborne human allergen, ragweed. The data showed that airway eosinophilia and mucus overproduction induced by ragweed were significantly reduced in CD1 KO mice, which was correlated with significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…In contrast, other investigators have found that coadministration of ␣-GalCer with antigen sensitizes mice to these antigens, thereby enhancing AHR (38,39). These seemingly contradictory results confirm that iNKT cells are critically involved in the regulation of AHR and indicate that the timing of activation of the iNKT cells dictates their role in AHR.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, other investigators have found that coadministration of ␣-GalCer with antigen sensitizes mice to these antigens, thereby enhancing AHR (38,39). These seemingly contradictory results confirm that iNKT cells are critically involved in the regulation of AHR and indicate that the timing of activation of the iNKT cells dictates their role in AHR.…”
Section: Discussionmentioning
confidence: 88%
“…Because conventional CD4 ϩ T cells alone do not appear to induce AHR in mouse models of asthma (15,16), we suggest that in many forms of asthma, iNKT cells are synergistic with conventional CD4 ϩ T cells in the induction of allergic pulmonary inflammation. First, iNKT cells may become activated early on and, by releasing IL-4 and IL-13, boost the priming of allergenspecific conventional CD4 ϩ T cells (38,39). Second, we suggest that inflammation or pulmonary injury induced by allergen-specific Th2 cells may modify or uncover self-glycolipid antigens, which then activate iNKT (effector) cells that directly induce AHR.…”
Section: Discussionmentioning
confidence: 91%
“…With regards to NKT cells, a number of reports have indicated that these cells are critical for the development of AHR in C57BL/6 mice, and these cells are also found in humans with asthma, although these findings are controversial (23,(63)(64)(65)(66)(67)(68)(69). We therefore also developed alternative networks that temporally place the ability of NKT cells secreting IL-13 prior to eosinophilderived IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this fundamental question in iNKT cell biology has remained elusive since almost all pathological experimental models of autoimmunity and asthma require an immunization phase that presumably recruits and activates iNKT cells in a non-physiological rather than a disease-specific manner. Hence, there is still no definite evidence that iNKT cells specifically exert natural regulatory functions in the experimental allergic OVA-or ragweed-induced asthma model, in which iNKT cells can promote disease protection [10,11] or induction and/or exacerbation [12][13][14], depending on their mode of activation.…”
Section: Introductionmentioning
confidence: 99%
“…The answer to this fundamental question in iNKT cell biology has remained elusive since almost all pathological experimental models of autoimmunity and asthma require an immunization phase that presumably recruits and activates iNKT cells in a non-physiological rather than a disease-specific manner. Hence, there is still no definite evidence that iNKT cells specifically exert natural regulatory functions in the experimental allergic OVA-or ragweed-induced asthma model, in which iNKT cells can promote disease protection [10,11] or induction and/or exacerbation [12][13][14], depending on their mode of activation.Here, we used a novel approach to address this issue in a model of innate-cell-driven lung inflammation induced by , a cytokine that has recently been described as a member of the IL-1 family [16] and credited with alarmin functions [17][18][19]. This strategy is of pathophysiological relevance, considering the well-established role played by iNKT cells during allergic asthma together with the fact that they are effectively targeted and functionally modified by 21].…”
mentioning
confidence: 99%